Les villes Islamiques au Maroc - Dossier d'enseignement pour instituteurs - Gaetano Palumbo (13911798) (2023)
This item is a Teacher Guide and Notes produced by UCL Qatar as part of the The Transformation of the Moroccan Landscape During the Early Islamic Period Project, and is part of Islamic Cities in Morocco School Pack - French collection.